Determination Of Micro Amount Of Spironolactone In Some Of Pharmaceutical Preparate By Using a Molecular Luminescence Technique. - Baghdad Science Journal (مجلة بغداد للعلوم)
The present study include a new developed method of analysis for determination of drug Spironolaction (SP) in some Pharmaceuticals by Spectrofluorometric method. Spironolaction was determined under optimal experimental condition that follows :- The excitation spectrum was (l=351 nm), the emmetion spectrum was (l=518 nm), pH=1, the suitable temperature for reaction 60oC and the optimal time less than (3) minute. The analysis and rang statistical data was:-Linear dynamic rang (1-10) ?g.ml-1, the detection limit (D.L = 0.023 ?g.ml-1), Molar absorptivity (? = 29875 liter mole-1 cm-1), Relative standard deviation (%RSD = 0.78), (%Erel = 3.3) and recovery (Rec = 96.6) percentage. Determination of Spironolactone was accomplished by two methods (A) Using direct calibration curve method, Corr. Coef. (R = 0.988 and %Rec = 97.4). (B) Using standard additional methods Corr. Coef (R =0.988 and %Rec= 96.6).